Megafans of the Northern Victorian Riverine Plains, SE Australia ... - Webb, John; Kapteinis, Karen; White, Susan (La Trobe, 2024)
This book provides a new inventory of nearly 300 megafans across five continents. Chapters focus on regional studies of megafans from all continents barring North America and Antarctica. ...